2003
DOI: 10.1186/1471-2156-4-s1-s82
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide linkage scan for genes affecting longitudinal trends in systolic blood pressure

Abstract: Only one genome scan to date has attempted to make use of the longitudinal data available in the Framingham Heart Study, and this attempt yielded evidence of linkage to a gene for mean systolic blood pressure. We show how the additional information available in these longitudinal data can be utilized to examine linkages for not only mean systolic blood pressure (SBP), but also for its trend with age and its variability. Prior to linkage analysis, individuals treated for hypertension were adjusted to account fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…There was little agreement in the linkage analysis results based on SBP in the FHS. Significant results in the same region were found by two groups on chromosomes 1 (200-240 cM) [James et al, 2003;Wang et al, 2003] and 12 (66-78 cM) [James et al, 2003;Jacobs et al, 2003].…”
supporting
confidence: 76%
“…There was little agreement in the linkage analysis results based on SBP in the FHS. Significant results in the same region were found by two groups on chromosomes 1 (200-240 cM) [James et al, 2003;Wang et al, 2003] and 12 (66-78 cM) [James et al, 2003;Jacobs et al, 2003].…”
supporting
confidence: 76%
“…In the Framingham Offspring Study, blood pressure slope and curvature over time during adulthood have been found to link to regions on chromosomes 7, 18, and 20. 12,13 In this study, we found a LOD peak at 28 cM from the p-terminal on chromosome 18 for the incremental AUC of diastolic blood pressure, a combination of linear slope and nonlinear curvature. Positive linkage has also been observed around this region for long-term blood pressure levels 10 and essential hypertension 36 in other studies.…”
Section: Chen Et Al Genetic Loci For Blood Pressure Since Childhood 957supporting
confidence: 49%
“…10,12,13 However, information on the genetic loci linking longitudinal changes in blood pressure from childhood to adulthood is still limited. Longitudinal observations from the Bogalusa Heart Study, a community-based epidemiologic study of early natural history of cardiovascular risk factors beginning in childhood, 14 provide an opportunity to examine the susceptibility loci influencing both between-person and within-person variability in blood pressure from childhood to young adulthood.…”
mentioning
confidence: 99%
“…Franke et al [2005] and Papanicolaou et al [2005] examined the issue of critical values. Franke et al [2005], using simulated data, examined a methodological issue concerning the family-wise weighting of H-E regression by marker informativity, as proposed by Jacobs et al [2003]. Specifically, they used a simplex weighting scheme to determine the applicability of designing asymptotically significant P-values.…”
Section: Genome-wide Scans: Methodological Issuesmentioning
confidence: 99%